PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWERPOINT DENGAN GAMIFIKASI PADA MATA PELAJARAN IPAS KELAS IV SDN 1 TEMPOS - Mukpi, Mona Febriyanti; Nurul Kemala Dewi; Setiani Novitasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an interactive learning media based on PowerPoint with gamification elements and to determine the validity and practicality levels of the developed media. Gamification is implemented through game elements such as challenge levels, points, and game rules designed to enhance students' motivation and engagement in the learning process. This research employs the Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Validation was carried out by two experts: a media validator and a material validator. Practicality testing was conducted through a small-group trial involving 6 fourth-grade students and a large-group trial involving 20 fourth-grade students and their homeroom teacher at SDN 1 Tempos. The results showed that the learning media achieved a validity level of 90,6% from the media validator and 92% from the material validator, both categorized as "very valid." The homeroom teacher’s response to the interactive PowerPoint-based learning media reached a percentage of 91,6%. Additionally, the practicality test with students indicated a practicality level of 91,6%, which also falls into the "very practical" category. Therefore, the interactive PowerPoint-based learning media with gamification is considered feasible and effective to be used as a supporting tool in the learning process to increase students’ participation and learning motivation.